Analysis and Experimental Study of Vibration System Characteristics of Ultrasonic Compound Electrical Machining - Deng, Z.Q.; Zhu, Y.W.; Wang, F.; Gu, X.; Yang, D. (Проблемы прочности, 2017)
The effect of applying ultrasonic vibration in the ultrasonic compound electrical machining is analyzed. According to the resonance system during machining and on the basis of vibration theory, the shape and dimension parameters of the ultrasonic amplitude transformer and the tool head are calculated and analyzed. The amplitude transformer and the tool head used in this experiment have been designed to meet the requirements of this investigation. Under different conditions, ultrasonic vibration parameters are measured online using the high-speed high-precision micro-displacement laser sensor. The obtained results show high accuracy and efficiency of the investigation. The relationship parameters between the ultrasound amplitude and the ultrasonic excitation voltage are obtained from the mathematical calculations. The results provide the basic conditions for online optimization of the ultrasonic compound electrical machining parameters. Meanwhile, the working stability of the ultrasonic vibration system and the technical advantages of the ultrasonic compound electrical machining method are verified using the analysis results. In order to do this, the processing parameters have been reasonably selected, while the ultrasound machining and ultrasonic compound electric machining have been tested on ceramics, carbide, and other hard yet brittle materials.